Rancang Bangun Website Sekolah Dengan Metode User Centered Design (studi Kasus: Sekolah Insan Teladan) - Siti Sri Maharani; Rika Perdana Sari (Politeknik Caltex Riau, 2021)
Insan Teladan School does not yet have a container containing school information as a promotional medium. So, we need a website school that functions as a forum for providing information so that people can access information more quickly. The purpose of this research is to build a school website with functionality that suits user needs and has an attractive appearance according to the user's wishes. The application of the method User Centered Design (UCD) that focuses on the needs and desires of users is expected to realize the research objectives. The UCD method applied is the use of user personas as the basis for designing mockups and prototypes. All system functionality has been fulfilled by conducting the User Acceptance Test which got 51 test items running well. Based on the 5 second test, it was found that 90% of prospective users had a good experience when using Insan Teladan School website the test Usability Testing resulted in the first highest score on the aspect satisfaction of 90.48% and the second highest score on the aspect learnability of 90, 38% so that it can be concluded that Insan Teladan School website has an attractive appearance and is user friendly.